Financial evaluation of cocoa mass spraying programme on the revenue generation of the Ghana cocoa board - ASANTE CHRIS OSEI (knust, 2024)
A thesis presented to department of accounting and finance, college of humanities and social science In partial fulfillment of the requirement for the award of degree of master of science in accounting and finance